Comparison of measured rain attenuation and ITU-R predictions on experimental microwave links in Malaysia - Abdulrahman, Amuda Yusuf (Cambridge University Press, 2011)
This paper presents the results of direct rain attenuation measurements carried out on four experimental microwave links, installed at UTM, Malaysia. The links operate at frequencies of 15, 22, 26, and 38 GHz and the cumulative distribution function for different rain rates have been generated from the measured 4-year rain gauge data. The experimentally measured attenuation data have been compared with International Telecommunication Union-R rain attenuation predictions; and it has been found that the latter have underestimated the measured values, especially at higher rain rates. The deviations have been modeled as a function of rain rate exceedances R%p. It is hoped that the study will provide useful information for estimation of rainfall attenuation on microwave links in tropical regions that have similar situation to Malaysia.